MARKETING COMMUNICATION STRATEGY OF HIGHER EDUCATION INSTITUTIONS (HEIS) IN ATTRACTING PROSPECTIVE STUDENTS: A CASE STUDY IN BANDUNG, WEST JAVA - Natasha Karina Djati; Funny Mustikasari Elita; Ira Mirawati (RADJA PUBLIKA, 2026)
This study aims to analyze Higher Education Institutions (HEIs) SY’s marketing communication strategy for attracting prospective students in the 2024/2025 academic year, highlighting key insights for marketing strategies in higher education. Amid intense competition among Higher Education Institutions (HEIs) in West Java, SY demonstrated resilience by increasing digital engagement by 20% post-pandemic. This Research employs a qualitative case study approach within a post-positivist paradigm. Data were collected through in-depth interviews, observation, and documentation. Data analysis followed the Miles and Huberman model, comprising data reduction, display, and conclusion drawing. The results indicate that SY successfully implemented a concentrated STP (Segmentation, Targeting, Positioning) model by shifting the institutional positioning from a mere 'degree provider' to 'career certainty' through international work-study programs. The integration of social media (Instagram, TikTok, and Facebook) as a persuasion engine proved effective in reaching Generation Z. At the same time, a hybrid management system involving professional creative vendors enhanced the visual quality of content. The study concludes that while digital strategies are highly effective at building awareness, final enrollment decisions remain deeply influenced by social validation and tangible alumni success stories, offering valuable insights for higher education marketing strategies.